A school culture of sport in the Evangelical Institute, Lavras, Minas Gerais (1893-1919) - Bruno Adriano Rodrigues Silva (Revista Brasileira de História da Educação, 2017)
The objective of this paper is to analyze from a historical point of view the relationship between sport and school in the Evangelical Institute (1893-1919). This educational institution stays in the city of Lavras, south of Minas Gerais and was founded by protestant missionaries from the Southern United States. We hypothesized that it developed a school culture of sport. In this case, we investigated its historical constitution and its characteristics as well as its interface with the sport. We used primary sources (documents, brochures and newspapers) and secondary (books and a thesis) as empirical material. We conclude that at the same time that the Educational institution was purposeful in relation to sports, it was also permeable to them,